Application of MOSkin detector for in vivo dosimetry on total skin electron therapy (TSET). (20th February 2018) - Choi, J H; Cutajar, D; Metcalfe, P; Downes, S
Abstract: Currently, TLDs and Gafchromic EBT3 film are commonly used for skin dose measurement during Total Skin Electron Therapy. However, measurements using these dosimeters are time consuming due to post-irradiation processing requirements. The MO Skin has advantages of being a small physical size with a 0.55 μ m thick gate oxide and a water equivalent depth of 0.07 mm while providing real-time dosimetry. Measurements of the MO Skin 's dosimetric characteristics were performed using a 6 MeV electron beam with an Elekta Infinity linear accelerator. For the TSET measurements, doses measured with the MO Skin were directly compared to TLDs and Gafchromic EBT3 film using a 6 MeV high dose rate electron beam. A 6 mm Perspex spoiler was placed and aligned perpendicularly to the beam in order to lower the effective beam energy and improve dose homogeneity. The MO Skin showed good dose linearity (R 2 = 0.9986) and dose rate independence for a 6 MeV electron beam and behaved very similarly to the other types of dosimeters that are commonly used in vivo dosimetry. For the TSET measurements, all three detector types showed a very similar trend of dose readings over the range of measurement points. Therefore, the MO Skin is an effective skin dosimeter for TSET dosimetry.